MENUMBUHKAN JIWA WIRAUSAHA MELALUI PENGEMBANGAN UMKM DENGAN MEMBANGUN USAHA OLAHAN MAKANAN LURING (LUMPIA KERING) DI DESA SUKAMANAH - Tabroni Tabroni; Maria Chriesty S; Susanti Susanti; Riwan S Siregar; Mila Rosa (Indonesian Collaboration Journal of Community Services, 2021)
The Covid-19 pandemic has had an impact on the Indonesian economy. The decline in economic performance is not only felt by large multinational and national companies, but also by MSME actors. The appeal to prevent the chain of spreading this virus requires people to stay at home. This has an impact on economic instability and one of those affected is MSMEs. For this reason, a survival strategy is needed for MSMEs to be able to continue to maintain their business in the midst of this pandemic. The implementation of the KKM Bina Bangsa University Banten in 2021 is to foster an entrepreneurial spirit in the community and build a business with a new concept by looking at the potential that exists in the community, then KKM 58 UNIBA carries out a Home Industry Business Idea to manufacture food products made from spring rolls which are processed into food. light. The results of this study recommend survival strategies for SMEs in the form of improving product quality and adding services as well as establishing and optimizing customer marketing relationships. The results of this study are important to be understood and adopted by MSME actors and it is hoped that MSME actors will always be responsive and adapt to environmental changes in order to survive